Influence of Various Heparin Preparations on Lipoproteins in Hemodialysis Patients: A Multicentre Study - Kronenberg, Florian; König, Paul; Neyer, Ulrich; Auinger, Martin; Pribasnig, Andreas; Meisl, Thomas; Pinter, Georg; Dieplinger, Hans (Thrombosis and Haemostasis, 1995)
Recent studies have indicated controversial effects of low molecular weight heparin (LMWH) on lipid metabolism in patients on chronic hemodialysis as compared to unfractionated heparin (UFH).We therefore conducted a cross-sectional multicentre study comparing 153 patients treated with LMWH and 153 patients with UFH, matched for sex, age and diabetes mellitus. Both groups have been treated with LMWH or UFH for six months or longer (14.9 vs.23.4 months). We observed no differences between the UFH and LMWH treatment groups for total cholesterol, LDL cholesterol, triglycerides, apoB, apoA-IV or Lp(a). The only significant differences were seen for HDL cholesterol and the corresponding apolipoprotein apoA-I, which were significantly higher in the UFH group (HDL cholesterol: 0.97 ± 0.35 mM/l vs. 0.87 ± 0.37 mM/l, p<0.05; apoA-I 1.23 ± 0.27 g/l vs. 1.15 ± 0.27 g/l, p <0.05).We conclude that the results of studies investigating the influence of LMWH on lipid metabolism are as heterogeneous as the substances themselves. This challenges the beneficial influence supposedly had by LMWH preparations on lipid metabolism.